1997
DOI: 10.1111/j.1439-0434.1997.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Virus on the Chlorophyll, Carotenoid and Polyamine Contents in Grapevine Microcuttings

Abstract: We have studied the effect of different types of virus infections on the content in chlorophylls, carotenoids and free polyamines in shoots of vine cv, Albarino cultured in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…To date, however, no consensus has been reached regarding the identification of the viral product(s) responsible for disease symptoms and the initial biochemical or molecular processes that are affected by the infection (Van Loon, 1987; Reinero and Beachy, 1989). Our results show that the contents of Chl and Car were significantly decreased in virus‐infected leaves, as previously described (González et al., 1997; Rahoutei et al., 2000; Christov et al., 2001). Chlorophyllase activity significantly reduced Chl a and Chl b contents in grapevine leaves.…”
Section: Discussionsupporting
confidence: 91%
“…To date, however, no consensus has been reached regarding the identification of the viral product(s) responsible for disease symptoms and the initial biochemical or molecular processes that are affected by the infection (Van Loon, 1987; Reinero and Beachy, 1989). Our results show that the contents of Chl and Car were significantly decreased in virus‐infected leaves, as previously described (González et al., 1997; Rahoutei et al., 2000; Christov et al., 2001). Chlorophyllase activity significantly reduced Chl a and Chl b contents in grapevine leaves.…”
Section: Discussionsupporting
confidence: 91%
“…Chlorophyll and carotenoid contents were strongly reduced in virus‐infected plants, as previously described (Abrasheva & Slavcheva, 1974; Balachandran et al ., 1994b; González et al ., 1997; Rahoutei et al ., 2000). However, chlorophyll fluorescence analysis suggests that virus‐induced damage to PSII was not the main factor limiting photosynthesis in infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection is especially problematic in crops because, unlike other diseases, its impact cannot be reduced by phytosanitary treatments. In grapevines ( Vitis vinifera ), in particular, a number of viruses are known to affect grape yield and quality (Walter, 1988; Credi & Babini, 1997; González et al ., 1997; Guidoni et al ., 1997; Cabaleiro et al ., 1999), with its important world‐wide economic impact (Walter & Martelli, 1996). Several studies have shown that virus‐infected grapevines present alterations of diverse metabolic processes, such as respiration, the activity of several enzymes, transport of assimilates, hormonal balance and photosynthesis (Pozsar et al ., 1969; Walter, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate individual polyamine content varies with grape cultivar, and results from this study show grape polyamine levels to differ among 'Pinot noir' rootstock/scion combinations as well. Gonzalez et al (1997) demonstrated that free polyamines in 'Albarino' shoots were impacted by vine virus status (GLRaV-3, GLRaV-1+ grapevine fleck disease, and GRSPaV). They also observed an increase in PUT, SPD, SPM, and total free polyamines in the leaves of vines with GLRaV-1 and grapevine fleck disease, or GRSPaV, compared to control vines.…”
Section: Resultsmentioning
confidence: 99%
“…Edreva (1997) reported a reduction in free polyamine, compared to control, in tobacco leaves inoculated with fungal, bacterial, or viral pathogens, and suspected the decrease was due to tissue damage rather than a direct affect of the pathogen. Gonzalez, Mosquera, San Jose, and Diaz (1997) reported an increase in free polyamines in 'Albarino' shoots that were infected with grapevine fleck disease and co-infected with GLRaV-1 or -3 or Grapevine rupestris stem pitting associated virus (GRSPaV), but did not report if GLRaVs affected polyamine levels in the fruit. To date, no literature has examined how GLRaVs might impact polyamine in 'Pinot noir' grapes.…”
Section: Introductionmentioning
confidence: 98%